Syntax and the brain: language evolution as the missing link(ing theory)? - Benítez-Burraco, Antonio; Progovac, Ljiljana (Frontiers in Psychology, 2024)
Our main argument is that neurolinguistic research on human language syntax would benefit greatly by expanding its scope to include evolutionary considerations, as it is precisely by taking them into account that one can address the apparent granularity mismatch between the abstract postulates of syntax and the concrete units of neurobiology. This entails considering flat(ter) syntactic structures, which have been hypothesized to approximate more ancestral forms of syntax, as well as non-propositional, emotional uses of language/syntax, including verbal aggression, which can be considered as older functions of language. Our evidence implicates cortico-striatal networks, whose dense connectivity is a relatively recent evolutionary development, and which largely overlap with the circuits of aggression, allowing us to identify a variety of ways of testing these hypotheses, extending them to both neurotypical and atypical populations. Finally, sound grounding in neurobiology of language should also ultimately inform syntactic theories themselves.